Pelatihan Pembuatan Media Pembelajaran dengan Program Autoplay untuk Guru-Guru SMPN 2 Balen Kecamatan Balen Kabupaten Bojonegoro - Fatiya Rosyida; Khofifatu Rohmah Adi (Universitas Negeri Malang, 2018)
Junior high school teachers have a responsibility to improve the quality of learning. Improving the quality of learning is accompanied by the demands of the times. In the 21st century, information technology is growing rapidly. Therefore, they have to foster their knowledge. The problem in SMPN 2 Balen is most teachers have not used the learning media. Though learning media have the power in transferring information. One of the IT-based media that can be used in learning is autoplay. Learning media with autoplay will make the learning process interesting so that students can be motivated in learning. This is because the program can display text, images, sound and video. Seeing the problems described above, it is necessary to do activities that can improve the ability of teachers in developing and utilizing IT-based learning media, through training of making learning media with autoplay program. This devotion activity aims to help teachers SMPN 2 Balen in improving the quality of learning, especially related to the pedagogical competence of teachers about knowledge and skills in developing and applying media learning with Autoplay program. Training is conducted for 6 months divided into three stages: (1) planning stage, (2) stage of implementation, (3) evaluation phase. Results from activities in the form of learning media products with autoplay program.